2003
DOI: 10.1177/0092070303254412
|View full text |Cite
|
Sign up to set email alerts
|

Angry Customers don't Come Back, They Get Back: The Experience and Behavioral Implications of Anger and Dissatisfaction in Services

Abstract: This article investigates the specific experience of anger and dissatisfaction and their effects on customers' behavioral responses to failed service encounters across industries. Study 1 demonstrates that anger and dissatisfaction are qualitatively different emotions with respect to their idiosyncratic experiential content. Study 2 builds on these findings and shows how anger and service encounter dissatisfaction differentially affect customer behavior. It provides empirical support for the contention that an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
712
1
19

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 722 publications
(770 citation statements)
references
References 57 publications
38
712
1
19
Order By: Relevance
“…was measured with a three item Likert scale: "I intend to switch to a competitor in the future", "I would favor the offerings of other telecom providers before my current telecom provider in the future" and "I will consider to switch telecom providers soon" (Bougie, et al, 2003;Harris & Goode, 2004;R. A. Ping, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…was measured with a three item Likert scale: "I intend to switch to a competitor in the future", "I would favor the offerings of other telecom providers before my current telecom provider in the future" and "I will consider to switch telecom providers soon" (Bougie, et al, 2003;Harris & Goode, 2004;R. A. Ping, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Next to sharing positive experiences and distributing recommendations for particular products, more and more consumers use the online medium to distribute unfavorable experiences. This so-called negative online word-of-mouth (negative O-WOM) consists of disclosed individual negative experiences and opinions about goods, services and organizations that have been formed during the post-consumption process (Bougie, Pieters, & Zeelenberg, 2003;Lee & Song, 2010). It is suggested that individuals are more honest in sharing their negative experiences online because the anonymity of a person on the Internet prevents them from facing any social consequences (Joinson, 2001;Yun & Park, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Além de ignorar as disputas históricas entre o departamento de Marketing e a alta hierarquia, que foram ressaltadas pelo âmbito da estratégia de marketing (Boxer e Wensley, 1986;Day e Wensley, 1983;Driver e Foxall, 1986), o conceito de OPM reforça e amplia as ideologias de mercado livre, empresa livre e consumidores livres construídas na Guerra Fria.…”
Section: Uma Análise Do Conceito De Opm No Contexto Da Globalizaçãounclassified
“…Isso explica o crescente interesse de pesquisadores por insatisfação do consumidor (Bougie et al, 2003;Chauvel, 2000) e por abordagens críticas extremas em marketing (veja Burton, 2001). Esses interesses recentes ecoam questionamentos históricos sobre a relevância da área e do poder efetivo do marketing para e na grande empresa e na sociedade (Hunt e Lambe, 2000;Varadarajan e Jayachandran, 1999;Brownlie et al, 1999).…”
Section: Introductionunclassified
“…When customers face a problem they may respond by exiting (Zswitching to another provider), loyalty (Zstaying with the supplier anticipating that 'things will get better') or voicing (Zcomplaining to the firm or word-of-mouth to third-parties) (Levesque & McDougall, 1996;Tax, Brown, & Chandrashekaran, 1998). Unfortunately, it is only the tip of the iceberg that complains to the company (Stephens & Gwinner, 1998) since dissatisfied customers tend to remain passive when experiencing a problem (Bougie, Pieters, & Zeelenberg, 2003).…”
Section: Introductionmentioning
confidence: 99%